2022
DOI: 10.3390/en15051882
|View full text |Cite
|
Sign up to set email alerts
|

Selection of an Appropriate Solar Thermal Technology for Solar Vapor Absorption Cooling—An MADM Approach

Abstract: Different solar thermal collectors have been used recently to meet the thermal requirements of single effect and double effect vapor absorption cooling systems, making selection of the correct method a challenge. Different attributes of each vapor absorption cooling and solar collector combination are taken into account, and a Multi-Attribute Decision-Making model is used to select the best option. The model requires variables indicating the performance of the system, which are called attributes that are organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Arsalis and Alexandrou [16] concluded that the SHC system has favorable running costs in comparison with an air-to-water vapor compression heat pump, but their estimations did not include auxiliary equipment electricity consumption, maintenance costs, or consumption and cost for water supplied to cooling towers due to evaporation. Kaneesamkandi et al [22] compared the absorption SHC system and vapor compression cooling system in the climatic zones of Niger, Riyadh and Beijing. They concluded that the absorption SHC shows an advantage in electricity consumption and emissions, but for better overall performance, additional cost reduction of equipment is required.…”
Section: Introductionmentioning
confidence: 99%
“…Arsalis and Alexandrou [16] concluded that the SHC system has favorable running costs in comparison with an air-to-water vapor compression heat pump, but their estimations did not include auxiliary equipment electricity consumption, maintenance costs, or consumption and cost for water supplied to cooling towers due to evaporation. Kaneesamkandi et al [22] compared the absorption SHC system and vapor compression cooling system in the climatic zones of Niger, Riyadh and Beijing. They concluded that the absorption SHC shows an advantage in electricity consumption and emissions, but for better overall performance, additional cost reduction of equipment is required.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable sources and waste heat become the best option when these sources are available; otherwise, directfired sources (such as the burning of fuel in the generator) will meet the requirement of multi-effect VACS when operated at night hours. Zakariya Kaneesamkandi et al [37] demonstrated an appropriate solar collector for the operation of single and double-effect VACS. A multi-attribute decision-making model was adopted to determine the best option.…”
Section: Introductionmentioning
confidence: 99%